Fathers and children from infancy to middle childhood - Emer Smyth; Helen Russell (The Economic and Social Research Institute (ESRI), 2021)
The influence of fathers on child experiences and outcomes has been given much less attention in international and Irish research than the influence of mothers (Fitzgerald et al., 2020). The Growing Up in Ireland (GUI) study has collected very detailed information from fathers throughout the different waves of the study which can be used to address this gap. This report uses data on the younger GUI cohort, Cohort '08, who were born in 2008 and were nine years of age in 2017. It documents the nature of father-child interaction and the quality of father-child relationships from infancy (nine months) to middle childhood (nine years). Analyses relate to the 4,090 cases where fathers and mothers were both living with the child and where fathers completed the survey at all full waves.1 However, additional analyses are included on the quality of the relationship between children and their non-resident fathers, as reported by the children at nine years. Case numbers did not permit an analysis of households with lone fathers or same-sex couples.
Keywords: 330; Väter; Kinder; Soziale Beziehungen; Freizeitverhalten; Stress; Irland